Humility and The Gift: The Elective Affinity of Institutions and Ethics in Orthodox Parishes - Zabaev, Ivan; Zueva, Anna; Koloshenko, Yuliya (Экономическая социология, 2015)
This article analyzes the economic ethics of modern Orthodox laity belonging to the Russian Orthodox Church. The article is based on an array of interviews with priests, and Orthodox laypersons (as well as non-believers and Catholics for comparison purposes). Data were collected via several projects from 2004 to 2014. Data (in-depth interviews from the recent projects 2012−2014 amount to 395) are analyzed by means of the grounded theory methods, including substantial and theoretical coding, theoretical sampling, and constant comparative method. Theories used include the concept of elective affinity between the motivation of economic activities and types of economic organization (Weber) and the typology of economic systems by K. Polanyi. This study attempts to show the elective affinity between the ethics of humility and the principle of economic integration known as reciprocity networks of mutual support of both churched and unchurched Russians, centered in the parishes and functioning on the basis of the logic of gift giving. Such a coupling of motivation and informal economy, invisible to the GDP, performs important functions in contemporary Russia which has a mix of economic types (such as generating of social capital or development of moral density and solidarity in local communities. They in it’s turn fulfill some economic functions — i.e. avoiding getting into the debt bondage or some others).The article deals with (the activated by humility ethics) reciprocity and its consequences for the community seeks to challenge the established view on Orthodox Christianity as an ‘unproductive’ culture, hindering economic development.